Evaluation of spring-applied endothall for annual bluegrass control in warm-season turf - John M. Peppers; Shawn D. Askew (Weed Technology, 2025)
Increasing instances of herbicide-resistant annual bluegrass have limited turf managers’ options for chemical control. Endothall inhibits serine threonine protein phosphatase, a novel site of action for warm-season turf, and endothall use in hybrid bermudagrass is not extensively reported. Greenhouse studies were conducted to evaluate herbicide-resistant annual bluegrass response to endothall. Five herbicide-resistant annual bluegrass biotypes were treated with increasing endothall rates and compared to two susceptible populations. One glyphosate-resistant annual bluegrass biotype was 2.3- to 3.3-fold more resistant to endothall depending on trial and susceptible biotype, and all other biotypes were endothall susceptible. Four field studies were established from 2022 to 2023 to evaluate the influence of endothall rate and application timing on bermudagrass and manilagrass turf injury and annual bluegrass control. These studies were arranged as a 3 × 4 factorial with three levels of application timing (fully dormant, 50% green, and 100% green) and four levels of herbicide (endothall applied at 1.12, 1.68, and 2.24 kg ai ha−1 and trifloxysulfuron applied at 27.8 g ai ha−1). Maximum observed turf injury was dependent on endothall rate and timing and was commercially acceptable (<30%) at the low and middle rates when applied to 100% green bermudagrass and at all rates when applied to dormant turf. When applied to 50% green turf (mid-transition), endothall unacceptably injured warm-season turf regardless of application rate. Endothall controlled annual bluegrass more effectively when applied during mid-transition and 100% green turf than it did when applied during fully dormant turf. When applied at rates of 1.68 and 2.24 kg ai ha−1 during mid-transition or at 100% green turf, endothall controlled annual bluegrass 83% to 95%. Results from these studies indicate that endothall selectively controls herbicide-resistant annual bluegrass in warm-season turf but that selectivity and performance depend on application timing.